Nanog maintains stemness of Lkb1‐deficient lung adenocarcinoma and prevents gastric differentiation. Issue 9 (7th September 2021) - Tong, Xinyuan; Chen, Yueqing; Zhu, Xinsheng; Ye, Yi; Xue, Yun; Wang, Rui; Gao, Yijun; Zhang, Wenjing; Gao, Weiqiang; Xiao, Lei; Chen, Haiquan; Zhang, Peng; et al.
Abstract :